Structure-property relations in ZrCN coatings for tribologic applications - Silva, E. (2010)
ZrCN coatings were deposited by dc reactive magnetron sputtering with N2 flows ranging from 2 to 10 sccm in order to investigate the influence of the nitrogen incorporation on structure and properties. Information about the chemical composition was obtained by glow discharge optical emission spectroscopy and Rutherford backscattering spectroscopy. The evolution of the crystal structure studied by X-ray diffraction revealed the formation of a face-centred cubic ZrCN phase for N2 flows greater than 4 sccm. Additionally, the presence of an amorphous phase in the coatings deposited with the highest N2 flows could be evidenced by Raman spectroscopy and X-ray photoelectron spectroscopy. This phase can act as a lubricant resulting in a low coefficient of friction as shown in the conducted ball-on-disc tests. Nanoindentation measurements showed that coatings deposited with a 6 sccm N2 flow had the maximum hardness which also revealed the best performance in the conducted dry cutting tests.